Pengendalian Kualitas Kemasan Produk Sarden 300 ml Menggunakan Metode Six Sigma (Studi Kasus : PT Ancol Terang Metal Printing Industri) - Nur Khaerani Busri; Nofias Fajri; Fidhiya Nanda Hasan (Jurnal Industri dan Teknologi Samawa, 2025)
PT Ancol Terang Metal Printing Industri is one of the industries engaged in manufacturing that produces packaging with metal raw materials. The problem faced by the company is the existence of defects in 300 ml Diameter Type Sardine Packaging products in 2022 and 2023 with an average defect value exceeding the 1% standard that has been set by the company. The purpose of this research is to control the quality of Sardine Packaging products with a diameter of 300 ml using the Six Sigma method through the DMAIC stage. Based on the results of the Define stage data analysis, 5 types of defects were obtained with CTQ: miss print, dent, scratch, welding and Internal Side Stripping. The Measure stage received a DPMO value of 3,137 in 2022 with a Sigma level of 4.21 and in 2023 of 3,871 with a Sigma level of 4.17 in the industry average category. The Analyze stage using pareto diagrams found that the types of defects that often occur are miss prints, dents and scratches. The causes of defects obtained from fishbone diagrams are humans, machines, methods and materials. The Improve stage that can be given to the company in general is to increase work supervision on operators, schedule machine control and make SOP schedules in the maintenance department, conduct training for operators and make material planning stock control cards to prepare more fresh ink materials in the prino department.